2020
DOI: 10.1186/s12889-020-09768-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and opportunities for cleanliness of shared sanitation facilities in low-income settlements in Kenya

Abstract: Background The sharing of sanitation facilities is a common practice in low-income areas in sub-Saharan Africa. However, shared sanitation is currently categorized as a limited sanitation service, and may therefore not count towards meeting the global goals. These shared facilities are often the only option available for most residents in low-income settlements, and improving their cleanliness and overall management is key to reducing open defecation and risk of disease. This study sought to investigate barrie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
(32 reference statements)
2
12
2
Order By: Relevance
“…Tenants generally were responsible for cleaning the toilets. This finding is consistent with other studies on cleaning arrangements for shared sanitation [ 37 , 38 ]. In more than half (57%) of compound houses in Ghana, all tenants were involved in cleaning the toilets while in less than half (44%) of compounds in Kenya, all tenants were involved in cleaning the toilets ( Table 3 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Tenants generally were responsible for cleaning the toilets. This finding is consistent with other studies on cleaning arrangements for shared sanitation [ 37 , 38 ]. In more than half (57%) of compound houses in Ghana, all tenants were involved in cleaning the toilets while in less than half (44%) of compounds in Kenya, all tenants were involved in cleaning the toilets ( Table 3 ).…”
Section: Resultssupporting
confidence: 93%
“…Similar to earlier studies [ 37 , 38 ], this study found that more compound houses have live-in landlords in Ghana than in Kenya and this could partly explain why reported cleaning frequencies of the sanitation facilities are higher than in Kenya. Shared sanitation facilities in Ghana were comparatively cleaner than those in Kenya.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, in urban areas <24% of the population has access to hand hygiene facilities. 12 , 15 This study found the prevalence of reported hand washing with water to be high (97%), while the prevalence of those who reported hand washing with soap and water was only 58%. This could be attributed to the health promotion activities that have been done by the Kenyan government on the importance of hand hygiene as a COVID-19 infection control measure.…”
Section: Discussionmentioning
confidence: 76%
“…The proportion of households sharing toilets/latrines in this study was higher than the Kenyan estimate of 44%. 15 …”
Section: Discussionmentioning
confidence: 99%